2021
DOI: 10.1111/sltb.12739
|View full text |Cite
|
Sign up to set email alerts
|

Comparing warning signs of suicide between suicide decedents with depression and those non‐diagnosed psychiatric disorders

Abstract: Objective: Early recognition of a high-risk group impending suicide is important. We aimed to compare warning signs depending on the nature of the psychiatric disorder and whether it was a documented diagnosis. Methods: Data of suicide decedents were collected from police records from 2013 to 2017. We evaluate psychiatric symptoms and warning signs in three aspects (language, behavior, and affect) using the Korea-Psychological Autopsy Checklist for Police Records (K-PAC-PR). Results: A total of 13,265 suicide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
1
6
2
Order By: Relevance
“…to catalog and examine such attacks. ALERRT has documented more than 433 such events, noting that "In more than a quarter of episodes, the attackers ended the shootings by turning the guns on themselves" [42][43][44][45][46][47][48]. Adam Lankford, a professor at the University of Alabama, also interviewed for the New York Times article, noted that "The share of attackers who die by suicide is most likely a fraction of those who have suicidal expectations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to catalog and examine such attacks. ALERRT has documented more than 433 such events, noting that "In more than a quarter of episodes, the attackers ended the shootings by turning the guns on themselves" [42][43][44][45][46][47][48]. Adam Lankford, a professor at the University of Alabama, also interviewed for the New York Times article, noted that "The share of attackers who die by suicide is most likely a fraction of those who have suicidal expectations.…”
Section: Discussionmentioning
confidence: 99%
“…While suicide is a low base rate event, vulnerability may be indicated through multiple factors, including the previous suicide attempts, chronic depression and physical illness, and substance abuse experienced by the decedent. Identifying warning signs have been seen in most individuals within the study, postmortem, most who had been diagnosed with a psychiatric disorder [41].…”
Section: Risk Factors For Attempted Suicidementioning
confidence: 99%
“…'Talking about dying or suicide' and 'apathetic behavior' were the most common warning signs. Applying the findings from Kim et al (2022) to our study may have some limitations because the older persons in our analysis had no records or history of diagnosed psychiatric disorders. Our study found that eight older persons (8/30) directly expressed warnings, such as talking about death or suicide.…”
Section: Poor Understanding Of Early Warning Signsmentioning
confidence: 99%
“…Research suggests that a majority of people with suicide ideation express warning signs. Kim et al (2022) found that 93% of suicide victims showed warning signs. These signs were observed more often in those diagnosed with psychiatric disorders, especially those with a depressive disorder.…”
Section: Poor Understanding Of Early Warning Signsmentioning
confidence: 99%
“…Yaseen et al (2019) proposed diagnostic criteria for predicting imminent suicide risk, namely the suicide crisis syndrome (SCS) 8) . However, one issue is that the warning signs do not necessarily arise only immediately before death by suicide 9) . One issue with the SCS is that it predicts post-discharge suicidal behaviour only in a limited number of cases 8) .…”
Section: Introductionmentioning
confidence: 99%